Estado, Relações Internacionais e Direitos Humanos: entre os lugares e o tempo de um direito humano à cooperação solidária - Camera, Sinara (Universidade do Vale do Rio dos Sinos, 2014)
Cooperation efforts as a means to establish international solidarity to overcome more accessible issues to (and within) States are presented amongst dynamics not less complex than their own problems which are intended to be solved. In the center of the cooperative States practices and the international collective, explicit practices of national interest and State power to dictate the rules of cooperation (usually the cooperators) are unveiled. On the other hand, there are States that commit with such rules so as to be deserving of solidarity of their peers (developing countries and the less advanced). Thus, the theme of the present thesis is in a field of strong tensions and discussions about the conditions of possibilities offered by the dynamics of international relations to the cooperation practice and development, as well as the articulation of its mechanisms with institutions/individuals of the receiving States, mainly the policies evidenced in the period post-Cold War. Therefore, the present research had as a main aim to answer the following questions: In what ways do the dynamics of international relations allow the solidary practice of an international cooperation, articulated to local institutions of receiving States? Would the inversion of international solidarity basis enable the construction of cooperative human right for the development within/of the place? For these questions the thesis was structured in three parts: the first is about the path taken by the State towards international society, proposing, in the First Chapter to analyze the historical constructions of state paradigms and its rights as well as international law. The second chapter dealt with the sovereign State and international solidarity, through internal contexts of rights assertion and economic liberalism; and external of imperialism and European expansion in the XIX century, beginning of the XX century; the postsecond war and post-Cold war. The Second Part approached the return of the international community to the State, analyzing, in the Third Chapter the State and the international society facing the search for the coexistence, in a context of dominance over the human rights as well as the globalization of law and economy and juridical pluralism. The fourth Chapter approached the sovereign acts and the international solidarity in the dynamics of rights imposition, from the coercion of international community and sharing responsibilities. The Third Part went the other way round: from the people to international community. In the Fifth Chapter cooperation and international solidarity were analyzed in a context of sharing responsibilities by the States and international community, facing the cooperation duty and global solidarity dynamics amongst cooperative and cooperator States (constitutional). Finally, in the Sixth Chapter, cooperation to development and the right to solidarity were approached, identifying the efforts in order to re-mean its contents as well as the possibility of establishing an altered base in the setting of international cooperation connections. The structure shows the comprehension of the inversion of international connection basis from an international right which is not necessarily made of or set in States, but rather in social basis. The possibilities to forge human rights of solidary cooperation pass by the people, by individuals who make receiving States which, by means of collaborative and emancipatory practices, may reach the mechanisms for the development within/of the place.
Keywords: Estado; Relações internacionais; Direitos humanos; Cooperação; Solidariedade; State; International relations; Human rights; Cooperation; Solidarity; ACCNPQ::Ciências Sociais Aplicadas::Direito